Digitalization of MSME Business Planning in Cigugurgirang Village, Parongpong, West Bandung Regency: - - Priyatiningsih, Katharina; Purwihartuti, Koernia; Karnawati, Hennidah; Setyowati, Tri; Angestiwi, Tiafahmi; Dewi Purnama, Putri; Firdanti, Khairina Hafsa; Rusmalinda, Sinta (International Journal of Community Service & Engagement, 2025)
This community service program aims to enhance the business management quality of Micro, Small, and Medium Enterprises (MSMEs) in Cigugurgirang Village by applying appropriate technology, specifically digitalization of business planning. The problems identified include the ineffective use of technology in business management, both for marketing, product, and process innovation, human resource competency, and limited access to capital as well as suboptimal management of the cost of goods sold. The solution to these problems by the Community Service team was carried out by designing a business planning guide using the design thinking approach, including survey activities, workshops, manual template preparation, training, digitalization, and trials. The manual template is accompanied by a guide to filling out business plans. From business ideas and marketing, human resource management, operations and production, to finance, training was provided. Business planning from manual templates was transformed into digital templates using Google Workspace devices, whose documents were stored in the cloud and accessed via Google Drive, utilizing QR codes for MSME users. The digitalization of business planning is expected to further assist MSMEs in increasing the effectiveness of technology use and enhancing business innovation capabilities